2008
DOI: 10.1074/jbc.m802543200
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Glial Cell Line-derived Neurotrophic Factor-Coreceptor Complex

Abstract: Glial cell line-derived neurotrophic factor (GDNF), a neuronal survival factor, binds its co-receptor GDNF family receptor ␣1 (GFR␣1) in a 2:2 ratio and signals through the receptor tyrosine kinase RET. We have solved the GDNF 2 ⅐GFR␣1 2 complex structure at 2.35 Å resolution in the presence of a heparin mimic, sucrose octasulfate. The structure of our GDNF 2 ⅐GFR␣1 2 complex and the previously published artemin 2 ⅐GFR␣3 2 complex are unlike in three ways. First, we have experimentally identified residues that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 47 publications
6
97
0
2
Order By: Relevance
“…First, agrin is a monomeric ligand, while the RET ligand GDNF functions as a homodimer (Wang et al 2006;Parkash et al 2008). Second, the formation of the agrin-LRP4 complex is a two-step synergistic process, while GFLs dimerize with GFRa in a 1:1 stoichiometry (Schlee et al 2006;Wang et al 2006;Parkash et al 2008). Finally, MuSK prebinds to its coreceptor, LRP4, before activation, while RET does not (Kim et al 2008;Zhang et al 2008).…”
Section: A Working Model Of Musk Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, agrin is a monomeric ligand, while the RET ligand GDNF functions as a homodimer (Wang et al 2006;Parkash et al 2008). Second, the formation of the agrin-LRP4 complex is a two-step synergistic process, while GFLs dimerize with GFRa in a 1:1 stoichiometry (Schlee et al 2006;Wang et al 2006;Parkash et al 2008). Finally, MuSK prebinds to its coreceptor, LRP4, before activation, while RET does not (Kim et al 2008;Zhang et al 2008).…”
Section: A Working Model Of Musk Activationmentioning
confidence: 99%
“…However, key differences exist between the agrin-LRP4 and GFL-GFRa interactions. First, agrin is a monomeric ligand, while the RET ligand GDNF functions as a homodimer (Wang et al 2006;Parkash et al 2008). Second, the formation of the agrin-LRP4 complex is a two-step synergistic process, while GFLs dimerize with GFRa in a 1:1 stoichiometry (Schlee et al 2006;Wang et al 2006;Parkash et al 2008).…”
Section: A Working Model Of Musk Activationmentioning
confidence: 99%
“…In addition, glial cell line-derived neurotrophic factor (GDNF), which is supplemented in our medium, was originally purified by heparin affinity chromatography (Lin et al, 1993) and has later been shown to interact with heparan sulfates (HSs; Rickard et al, 2003). HSs are required for GDNF signaling through the GFRα1-RET complex (Barnett et al, 2002;Parkash et al, 2008). The addition of heparin at a final concentration of 25-50 U/ml resulted in a more than twofold improvement in the yield of GFP-positive spermatogonia after 21 days of culture (Fig.…”
Section: Propagation Of Sscs In Culturementioning
confidence: 99%
“…Similar to other RTKs, Ret functions as a homodimer. In agreement with the two-fold symmetry of the ligands (Eigenbrot and Gerber, 1997), crosslinking and high-resolution structural studies have shown that GFRas also interact with GDNF proteins as homodimers (Jing et al, 1996;Trupp et al, 1998;Wang et al, 2006;Parkash et al, 2008). Association between Ret and GFRas has also been detected (Sanicola et al, 1997;Eketjäll et al, 1999;Cik et al, 2000), so the functional receptor complex for GDNF ligands is therefore likely to conform to a 2:2:2 stoichiometry [ Fig.…”
Section: Multisubunit Receptor Complexes For Neurotrophic Factorsmentioning
confidence: 64%